Comparison of Remote Electrical Neuromodulation and Standard-Care Medications for Acute Treatment of Migraine in Adolescents: A Post Hoc Analysis. Issue 4 (29th June 2021) - Hershey, Andrew D; Irwin, Samantha; Rabany, Liron; Gruper, Yaron; Ironi, Alon; Harris, Dagan; Sharon, Roni; McVige, Jennifer
Abstract: Objective: There is an unmet need for new, efficacious, well-tolerated, acute treatments for migraine in adolescents. Remote electrical neuromodulation (REN) is a novel, nonpharmacological treatment that provides significant symptom relief with good tolerability. The current post hoc analysis compared the efficacy of REN to that of standard-care medications for the acute treatment of migraine in adolescents. Design: Within-participant post hoc analysis of data from a clinical trial. Setting: Data from a clinical trial. Subjects: Data from 35 adolescent participants were analyzed. Methods: Efficacy was compared between a run-in phase, in which attacks were treated with standard-care medications (triptans or over-the-counter medications), and an intervention phase, in which attacks were treated with REN. Efficacy was compared within participants through the use of McNemar's test at four endpoints (2 hours after treatment): single-treatment pain freedom and pain relief, and consistency of pain freedom and pain relief (defined as response in at least 50% of the available first four treatments). Results: At 2 hours after treatment, pain freedom was achieved by 37.1% of the participants with REN, vs 8.6% of the participants with medications ( P  = 0.004). Pain relief was achieved by 71.4% with REN, vs 57.1% with medications ( P  = 0.225). Consistency of pain freedom was achieved by 40% with REN, vs 8.6% with medications ( P  < 0.001). Consistency of pain relief was achieved by 80.0% with REN, vs 57.2% with medications ( P  = 0.033). Conclusions: Our results suggest that REN may have higher efficacy than certain standard-care medications for the acute treatment of migraine in adolescents. A larger-scale, blinded comparative-effectiveness and tolerability study is needed.